The Impact of Covid-19 Pandemic on Different Sectors of the Indian Economy: A Descriptive Study - Sidhu, Gurpreet Singh; Rai, Jaskirat Singh; Khaira, Kanwarvir Singh; Kaur, Sarabjit (International Journal of Economics and Financial Issues, 2020)
COVID-19 is changing the world we live in for the worst, and almost all parts of the world are stuck with hung economies and people's lockdown in their homes. This pandemic is not only taking a toll out of health care systems and peoples' lives but also its impacting world economies and resulting in job losses, business disruptions and making us head towards one of the worst times ever for people on earth. Almost, all the industries are undergoing massive declines in their businesses, and the impact is that much gigantic of this pandemic, that they are projecting worse times ahead. This paper focuses on different industries, which are most affected by the pandemic and how this results in job losses and the world economy. Keywords: Covid-19, Indian economy, Industries fallout, Recession. JEL Classifications: E44, O5 DOI: https://doi.org/10.32479/ijefi.10461